Automation and human relations with the private vehicle: from automobiles to autonomous cars - Sandry, Eleanor (University of Queensland, School of English, Media Studies & Art History, 2018)
© 2017, © The Author(s) 2017. This article theorises interactions between drivers, cars and their surroundings. It uses Don Ihde’s four human–technology relations – embodiment, hermeneutic, alterity and background – to analyse the ways in which human–car relationships develop through the process of driving. When driving non-autonomous cars, humans are engaged with cars in driver–car assemblages, within which they are aware of not only the car and how they control its movement but also the road and environmental conditions conveyed through the car. In autonomous and semi-autonomous cars, the connection between driver and car, process of driving and surrounding environment is disrupted. This may be regarded as a positive change, freeing drivers from the work of driving to enjoy rest and entertainment as they become passengers; however, as the car moves into a background relation with people inside the vehicle, it can become difficult for a human to take back control of the driving process with little warning.